Housing prices and trade surpluses in China: An inter-temporal approach. (February 2021) - Chen, Qiuyu; Feng, Ling; Li, Zhiyuan; Lin, Ching-Yi
Abstract: This paper develops an inter-temporal current account model to study the impacts of expected rising housing prices on trade surpluses in China. The model shows two channels working in opposite directions. The first channel is the intra-temporal substitution channel. It discourages current consumption of tradable goods, leading to trade surpluses. The second is the inter-temporal substitution channel, which instead leads to trade deficits. When intra-temporal channel dominates, expected rising housing prices lead to trade surpluses. However, borrowing constraints on housing purchases may weaken the intra-temporal substitution channel and thus weaken the positive correlation between expected housing prices and trade surpluses. We show empirically that expected rising housing prices lead to trade surpluses in China. We also identify possible reason for this finding: strong intra-temporal substitution elasticity due to large male to female sex ratio in China. We further show that the positive relation between expected rising housing prices and trade surpluses is weaker in regions with more stringent borrowing constraints, consistent with our model's prediction.